(3GdLOhi GdEbJUGOjI ddeTQhYGJ GdESJKeGQjI hbjGS GdQHMjI GdJLGQjI hGdbhejI (B/s - (3YHO GdYRjR , SejQ eMeOs ((3GdGScfOQjI(B: s (3ecJHI GdETYGY GdafjI(B, s, 2005)
(3GdOQGSI GdJaUjdjI ddQHMjI GdJLGQjI(B- (3JMdjd GdQHMjI GdbhejI ddeTQhY(B- (3OQGSGJ hMGdGJ JWHjbjIs
Keywords: (3GdESJKeGQs; (3GdeTQhYGJs; (3OQGSI GdLOhis